Dune dynamics safeguard ecosystem services. (15th November 2017) - Van der Biest, K.; De Nocker, L.; Provoost, S.; Boerema, A.; Staes, J.; Meire, P.
Abstract: Intensively used coastal zones often know a history of hard defense structures to prevent erosion and protect infrastructure against floods. The interruption of sand transport between sea, beach and dunes however causes a domination of late successional stages such as dune shrub. With the decline of young, dynamic vegetation types, a change occurs in the provision of ecosystem services. In spite of the growing awareness on the role of dune dynamics to support human well-being and biodiversity, redynamisation of dunes is rarely implemented in coastal zone management. It has been argued in research documents that this may be caused by a failure to make those benefits tangible and specific. This study aims to underpin the added value of dynamic versus fixed dunes. Five different ecosystem services in a case-study in Belgium were quantified based on (compound) indicators and expressed in monetary units. The value of a natural, dynamic dune system covering the entire gradient of dune succession and dominated by young successional stages was compared with the value of a fixed dune system dominated by late successional stages. The results indicate that a dynamic dune complex may create up to ∼50% higher economic benefits, and that the main benefits are on account of recreation and coastal safety maintenance. The results underpin the statement that we can only continue benefitting from the services dunes provide if we accept their mobile nature, but that redynamisation requires a site-specific feasibility analysis. Highlights: We quantified and monetized the value of the different stages in dune succession. Dynamic dunes may create up to ∼50% higher economic benefits then fixed dunes. The main benefits of dynamic dunes are recreation and coastal safety maintenance. Dunes should remain dynamic to safeguard their biodiversity values and ecosystem services.